Long-acting corrosion-resistant polyaspartic acid ester polyurea composite coating as well as preparation method and application thereof
By using polydopamine-modified graphene oxide as filler in polyaspartate polyurea coating, the defects of the coating during curing and service are solved, significantly improving the mechanical and corrosion resistance of the coating and extending the service life of the equipment.
Patent Information
- Application Number
- CN202510225977.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-05-27
AI Technical Summary
Polyaspartate polyurea coatings are prone to pores and cracks during curing and service, resulting in accelerated penetration of corrosive media and reduced the service life of the equipment.
By dispersing graphene oxide in a buffer solution and reacting with dopamine-hydrochloric acid, polydopamine-modified graphene oxide is formed, mixed with aspartate, and isocyanate-based curing agent is added to prepare a modified graphene oxide-enhanced aspartate polyurea coating.
It significantly improves the mechanical properties and corrosion resistance of the coating, enhances the adhesion between the coating and the metal matrix, extends the time when the corrosive media reaches the metal surface, and improves the overall protective performance of the coating.
Smart Images

Figure CN120041064A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of corrosion and protection coatings, and particularly relates to a long-lasting corrosion-resistant polyaspartic acid ester polyurea composite coating, a preparation method thereof, and an application thereof. Background Art
[0002] The development and utilization of various marine resources are the cornerstone for boosting the high-speed development of the national marine economy. Among them, the long-term and stable service of marine engineering equipment and ships is the guarantee for marine resource development. However, marine engineering equipment has been in service in a harsh environment of high salt, high humidity, high temperature, and strong ultraviolet radiation for a long time. Corrosion and its coupled damage are one of the main factors causing its shortened lifespan and safety accidents. Practice has proved that organic coatings play an important role in protecting marine engineering equipment and extending its service life. Among them, polyaspartic acid ester polyurea coatings are environmentally friendly and have good corrosion resistance, and are widely used in the protection of marine engineering equipment. However, during the curing and service processes, pores and cracks will occur in the coating. At the same time, in the actual application process, in this case, the penetration of corrosive media will accelerate the deterioration of the metal properties, thereby shortening the service life of the equipment. Therefore, how to reduce the internal defects of the coating, improve its mechanical properties and corrosion resistance, and thus extend the service life of marine engineering equipment is a technical problem that technicians in the field of corrosion and protection urgently need to solve.
[0003] Aiming at the problem of defects existing in the polyaspartic acid ester polyurea coating during the curing and service processes, the existing solutions usually involve adding nano-fillers to modify the coating. However, not all nano-fillers can exhibit good compatibility with polyaspartic acid ester polyurea. Therefore, directly adding nano-fillers may damage the integrity of the internal structure of the coating, resulting in a decline in the comprehensive protection performance of the coating. Graphene oxide two-dimensional sheets are widely used to reduce internal defects of the coating and block the penetration of corrosive media. However, defects often exist on the surface of graphene oxide two-dimensional sheets, and graphene oxide belongs to inorganic substances, and its incorporation into polyaspartic acid ester polyurea has poor compatibility, and there are weak regions at the filler / resin interface. Therefore, if the surface defects of graphene oxide can be repaired and the compatibility between the filler and polyaspartic acid ester polyurea can be improved simultaneously, it is expected to greatly improve the mechanical and corrosion resistance of the coating and extend the service life of the coating.
[0004] Patent CN118931250A proposes a modified graphene oxide and polyurea anticorrosive coating. Under the protection of an inert atmosphere, isocyanate group silane is used to modify graphene oxide to obtain modified graphene oxide, and then polyurea anticorrosive coating is prepared. The formed coating has strong adhesion to the metal substrate and can improve the barrier corrosion resistance to corrosive media. However, the overall coating preparation process is extremely complex and the process conditions are harsh. Not only does it require the modification of graphene oxide, but it also requires the compounding of bisphenol F epoxy resin and a stable rust converter to modify the polyurea anticorrosive coating to enhance the adhesion between the polyurea anticorrosive coating and the metal substrate. When only using isocyanate group silane to modify graphene oxide, according to the test of GB / T 5210-2006, its adhesion is only 9.0 Mpa and its corrosion resistance is limited. Summary of the Invention
[0005] The object of the present invention is to overcome the defects and deficiencies of the existing polyurea coatings, and provide a preparation method of an aspartic acid ester polyurea coating enhanced by modified graphene oxide, which can greatly improve the compatibility between the filler and the polyurea resin, reduce the internal defects of the coating, effectively improve the adhesion between the coating and the metal matrix, and enhance the corrosion resistance of the coating.
[0006] Another object of the present invention is to provide an aspartic acid ester polyurea coating.
[0007] Another object of the present invention is to provide the application of the above-mentioned aspartic acid ester polyurea coating in the preparation of marine engineering equipment protective materials.
[0008] Another object of the present invention is to provide a coated article, including a coating formed by curing the above-mentioned polyurea coating, which has good mechanical properties and corrosion resistance.
[0009] The above objects of the present invention are achieved by the following technical solutions:
[0010] The present invention protects a preparation method of an aspartic acid ester polyurea coating, including the following steps:
[0011] S1, disperse graphene oxide in a buffer solution, add dopamine hydrochloride and stir to react to obtain polydopamine-modified graphene oxide; the mass ratio of the graphene oxide to dopamine hydrochloride is 1:(0.5 - 3);
[0012] S2, uniformly mix the polydopamine-modified graphene oxide and aspartic acid ester, add an isocyanate curing agent and mix uniformly to obtain an aspartic acid ester polyurea coating.
[0013] In the aspartic acid ester polyurea coating of the present invention, graphene oxide modified with dopamine hydrochloride is used as a filler to improve the mechanical properties and corrosion resistance of the formed coating. Among them, dopamine hydrochloride, as a modifier, can enhance the compatibility between graphene oxide nanosheets and polyaspartic acid ester polyurea. At the same time, dopamine undergoes self-polymerization on the surface of graphene oxide to form a polydopamine layer with good adhesion, which can repair the surface defects of graphene oxide nanosheets, improve the coating density, extend the time for corrosive media to reach the metal surface, and also improve the adhesion between the coating and the metal substrate.
[0014] It should be noted that the present invention also controls the mass ratio of graphene oxide to dopamine hydrochloride within the range of 1:(0.5 - 3). This can utilize the high specific surface area of graphene oxide to widely cover and repair the micro-defects of the coating. At the same time, the modification with a specific amount of dopamine partially reduces graphene oxide, and some organic functional groups on the surface of graphene oxide are still retained. The synergistic effect with the self-polymerized polydopamine is better compatible with the polyaspartic acid ester polyurea coating matrix, improving the mechanical properties and corrosion resistance of the coating. In addition, polydopamine itself has a certain corrosion inhibition function and can also provide a certain corrosion inhibition effect in the initial stage of coating damage. If the content of dopamine hydrochloride is too low, the surface modification of graphene oxide will be incomplete, affecting the improvement effect. If the amount of dopamine hydrochloride is too much, the filler lamellae will agglomerate too thickly, which is not conducive to the wide coverage and repair of the coating micro-defects. Even more seriously, graphene oxide will be over-reduced to graphene or graphite, causing some physicochemical properties of the filler to change.
[0015] In some embodiments, in step S1, the buffer solution is tris(hydroxymethyl)aminomethane buffer solution (Tris), and the pH value is 7 - 9.
[0016] In some embodiments, in step S1, the temperature of the stirring reaction is 25 - 80 °C, and the reaction time is 5 - 32 h.
[0017] In some embodiments, in step S2, the mass ratio of the polydopamine-modified graphene oxide to the polyaspartic acid ester is (0.05 - 0.5):10.
[0018] In some embodiments, in step S2, the dosage of the isocyanate curing agent is 65 - 80 wt.% of the polyaspartic acid ester. In order to ensure the complete curing of the polyaspartic acid ester in the present invention, the dosage of the curing agent can be appropriately excessive to achieve room temperature curing, thus increasing the operability of the coating.
[0019] Optionally, the isocyanate curing agent is hexamethylene diisocyanate-based polyisocyanate.
[0020] In some of these embodiments, in step S2, when the polydopamine-modified graphene oxide and the aspartate ester are uniformly mixed, a diluent is further added, and the mass ratio of the polyaspartate ester to the diluent is 10:(3-6).
[0021] In some of these embodiments, in step S2, the diluent is at least one of butyl acetate, xylene or propylene glycol methyl ether acetate. The introduction of the diluent can improve the dispersion of the filler in the resin system and also reduce the viscosity of the coating, which is more conducive to the coating and leveling of the coating.
[0022] The present invention protects an aspartate ester polyurea coating, which is made by the preparation method of the aspartate ester polyurea coating described above.
[0023] The present invention protects the application of an aspartate ester polyurea coating in the preparation of protective materials for ocean engineering equipment.
[0024] The present invention protects a coated article, which is made by at least partially applying the aspartate ester polyurea coating on a metal substrate and curing to form a coating.
[0025] Optionally, the preparation method of the aspartate ester polyurea coating is: applying the aspartate ester polyurea coating on the surface of a metal substrate, and after drying and curing, a polydopamine-modified graphene oxide / polyaspartate ester polyurea composite coating is obtained on the surface of the metal substrate.
[0026] Optionally, the metal substrate is at least one of carbon steel, aluminum alloy, titanium alloy, magnesium alloy or copper alloy.
[0027] Optionally, the drying and curing temperature is 25°C to 60°C, and the curing time is 24h to 72h.
[0028] Optionally, the thickness of the coating is 50 to 200 μm.
[0029] Compared with the prior art, the beneficial effects of the present invention are:
[0030] The present invention provides a preparation method of an aspartate ester polyurea coating, using dopamine-hydrochloride modified graphene oxide as a filler to improve the mechanical properties and corrosion resistance of the formed coating; among them, dopamine-hydrochloride as a modifier can improve the compatibility between graphene oxide nanosheets and polyaspartate ester polyurea, and at the same time dopamine undergoes self-polymerization on the surface of graphene oxide to form a polydopamine layer with good adhesion, which can repair the surface defects of graphene oxide nanosheets, improve the coating density, extend the time for corrosive media to reach the metal surface, and also improve the adhesion between the coating and the metal matrix. Brief Description of the Drawings
[0031] Figure 1Morphology and structure of GO-PDA and GO in Example 1 and the elemental distribution map of GO-PDA.
[0032] Figure 2 Comparison chart of the adhesion of the coatings prepared in Example 1 and Comparative Examples 1-3.
[0033] Figure 3 Electrochemical impedance spectroscopy diagrams of the coatings prepared in Example 1 and Comparative Examples 1-2. Detailed implementation manners
[0034] The present invention will be further described below in conjunction with the detailed implementation manners, but the examples do not impose any form of limitation on the present invention. Unless otherwise specified, the raw material reagents used in the embodiments of the present invention are conventional raw material reagents purchased.
[0035] The following examples and comparative examples include the following raw materials:
[0036] Graphene oxide: JCGO-1-50, Nanjing Jicang Nano Technology Co., Ltd.
[0037] Polyaspartate ester: F520, Shenzhen Feiyang Junyan New Materials Co., Ltd.
[0038] Curing agent: Hexamethylene diisocyanate-based polyisocyanate, HT-600, Shenzhen Feiyang Junyan New Materials Co., Ltd.
[0039] Example 1
[0040] A method for preparing an aspartate ester polyurea coating, comprising the following steps:
[0041] (1) Prepare a polydopamine-modified graphene oxide composite material:
[0042] Disperse 0.15 g of graphene oxide ultrasonically in 150 mL of 10 mM tris(hydroxymethyl)aminomethane buffer solution, add dilute hydrochloric acid to adjust the solution to pH = 8.5, then add 0.3 g of dopamine hydrochloride, and stir and react in a water bath at 60 °C on a magnetic stirrer for 24 h to obtain a black suspension. Subsequently, centrifuge and separate, and then wash with absolute ethanol 3 times to obtain a black slurry-like polydopamine-modified graphene oxide composite material (GO-PDA).
[0043] (2) Prepare a composite material-modified polyaspartate ester polyurea:
[0044] Mix polyaspartate ester, GO-PDA and a diluent with a mass ratio of 10:0.17:4.3, wherein the diluent is butyl acetate. After high-speed centrifugal mixing for 3 min, add a curing agent accounting for 66.3 wt.% of the mass of the polyaspartate ester, and after high-speed centrifugal mixing for 3 min, a composite material-modified polyaspartate ester polyurea coating is obtained.
[0045] (3) Coating film layer:
[0046] Coat the composite material modified polyaspartic acid ester polyurea coating obtained in step (2) on the surface of Q235 carbon steel substrate that has been surface-treated (polished with 60-mesh to 220-mesh abrasive, then ultrasonically cleaned with degreasing liquid to remove oil stains and impurities on the surface, and finally dried the surface of the sample using an oven). After drying and curing in an oven at 60 °C for 48 h, a GO-PDA / polyaspartic acid ester polyurea composite coating is obtained on the Q235 carbon steel surface. The dry film thickness of the composite coating is 100 ± 10 μm.
[0047] Example 2
[0048] A method for preparing an aspartic acid ester polyurea coating, comprising the following steps:
[0049] (1) Preparation of polydopamine-modified graphene oxide composite material:
[0050] Ultrasonically disperse 0.3 g of graphene oxide in 200 mL of 10 mM tris(hydroxymethyl)aminomethane buffer solution, add dilute hydrochloric acid to adjust the solution to pH = 8.0, then add 0.15 g of dopamine hydrochloride, and stir and react in a water bath at 25 °C on a magnetic stirrer for 32 h to obtain a black suspension. Subsequently, centrifuge and separate, and wash twice with deionized water and anhydrous ethanol respectively to obtain a black slurry-like polydopamine-modified graphene oxide composite material (GO-PDA).
[0051] (2) Preparation of composite material modified polyaspartic acid ester polyurea:
[0052] Mix polyaspartic acid ester, GO-PDA and diluent with a mass ratio of 10:0.4:5, wherein the diluent is propylene glycol methyl ether acetate. After high-speed centrifugal mixing for 5 min, add a curing agent accounting for 69.7 wt.% of the mass of the polyaspartic acid ester, and obtain a composite material modified polyaspartic acid ester polyurea coating after high-speed centrifugal mixing for 5 min.
[0053] (3) Coating film layer:
[0054] Coat the composite material modified polyaspartic acid ester polyurea coating obtained in step (2) on the surface of the surface-treated aluminum alloy substrate. After drying and curing in an oven at 60 °C for 48 h, a GO-PDA / polyaspartic acid ester polyurea composite coating is obtained on the aluminum alloy surface. The dry film thickness of the composite coating is 80 ± 5 μm.
[0055] Example 3
[0056] A method for preparing an aspartic acid ester polyurea coating, comprising the following steps:
[0057] (1) Preparation of polydopamine-modified graphene oxide composite material:
[0058] Disperse 0.15 g of graphene oxide ultrasonically in 120 mL of 10 mM tris(hydroxymethyl)aminomethane buffer solution, adjust the solution to pH = 9.0 by dropping dilute hydrochloric acid, then add 0.45 g of dopamine hydrochloride, and stir and react in a water bath at 80 °C on a magnetic stirrer for 18 h to obtain a black suspension. Subsequently, centrifuge and separate, and then wash with absolute ethanol 4 times to obtain a black slurry-like polydopamine-modified graphene oxide composite material (GO-PDA).
[0059] (2) Preparation of composite material-modified polyaspartate polyurea:
[0060] Mix polyaspartate, GO-PDA and a diluent with a mass ratio of 10:0.5:6, where the diluent is xylene. After high-speed centrifugal mixing for 4 min, add a curing agent accounting for 75 wt.% of the mass of the polyaspartate, and after high-speed centrifugal mixing for 5 min, a composite material-modified polyaspartate polyurea coating is obtained.
[0061] (3) Coating the film layer:
[0062] Coat the composite material-modified polyaspartate polyurea coating obtained in step (2) on the surface of the aluminum alloy substrate that has been surface-treated, and place it in an oven at 60 °C for drying and curing for 48 h. Then, a GO-PDA / polyaspartate polyurea composite coating is obtained on the aluminum alloy surface, and the dry film thickness of the composite coating is 120 ± 10 μm.
[0063] Comparative Example 1
[0064] A preparation method of a polyaspartate polyurea coating, which is different from Example 1 in that there is no polydopamine-modified graphene oxide in this comparative example. The specific steps are as follows:
[0065] (1) Preparation of polyaspartate polyurea coating:
[0066] Mix polyaspartate and a diluent with a mass ratio of 10:4.3, where the diluent is propylene glycol methyl ether acetate. After high-speed centrifugal mixing for 3 min, add a curing agent accounting for 66.3 wt.% of the mass of the polyaspartate, and after high-speed centrifugal mixing for 3 min, a polyaspartate polyurea coating is obtained.
[0067] (2) Coating the film layer:
[0068] The polyaspartic ester polyurea coating obtained in step (1) was coated on the surface of a Q235 carbon steel substrate that had been surface-treated (polished from 60 mesh to 220 mesh, then ultrasonically cleaned with a degreasing solution to remove oil stains and impurities on the surface, and finally the surface of the sample was dried using an oven). After being placed in an oven at 60 °C for drying and curing for 48 h, a polyaspartic ester polyurea coating was obtained on the Q235 carbon steel surface, and the dry film thickness of the coating was 100 ± 10 μm.
[0069] Comparative Example 2
[0070] A method for preparing a polyaspartic ester polyurea coating, which is different from Example 1 in that: unmodified graphene oxide is added to the polyaspartic ester polyurea in this comparative example, and the specific steps are as follows:
[0071] (1) Prepare a polyaspartic ester polyurea coating:
[0072] Mix polyaspartic ester, GO, and a diluent with a mass ratio of 10:0.17:4.3, where the diluent is propylene glycol monomethyl ether acetate. After high-speed centrifugal mixing for 3 min, a curing agent accounting for 66.3 wt.% of the mass of the polyaspartic ester is added, and a modified polyaspartic ester polyurea coating is obtained after high-speed centrifugal mixing for 3 min.
[0073] (2) Coat the film layer:
[0074] The modified polyaspartic ester polyurea coating obtained in step (1) was coated on the surface of a Q235 carbon steel substrate that had been surface-treated (polished from 60 mesh to 220 mesh, then ultrasonically cleaned with a degreasing solution to remove oil stains and impurities on the surface, and finally the surface of the sample was dried using an oven). After being placed in an oven at 60 °C for drying and curing for 48 h, a GO / polyaspartic ester polyurea composite coating was obtained on the Q235 carbon steel surface, and the dry film thickness of the composite coating was 100 ± 10 μm.
[0075] Comparative Example 3
[0076] A method for preparing a polyaspartic ester polyurea coating, which is different from Example 1 in that: silane-modified graphene oxide is used in this comparative example, and the specific steps are as follows:
[0077] (1) Prepare silane-modified graphene oxide
[0078] Disperse 0.15 g of graphene oxide ultrasonically in 150 mL of deionized water. Mix deionized water and absolute ethanol at a volume ratio of 1:4 to form a 200 mL solution. Adjust the pH of the solution to 3 with 0.5 mol / L oxalic acid solution, then add 1 g of a 5% (volume fraction) silane coupling agent (KH-550), and stir and hydrolyze in a water bath at 35 °C for 2 h. Add the hydrolyzed silane coupling agent solution to the dispersed graphene oxide dispersion, and stir and react in a water bath at 65 °C for 12 h. Subsequently, perform centrifugal separation, and then wash with absolute ethanol three times to obtain silane-modified graphene oxide.
[0079] (2) Preparation of polyaspartate polyurea:
[0080] Mix polyaspartate, silane-modified graphene oxide, and a diluent at a mass ratio of 10:0.17:4.3, where the diluent is propylene glycol methyl ether acetate. After high-speed centrifugal mixing for 3 min, add a curing agent accounting for 66.3 wt.% of the mass of the polyaspartate, and then perform high-speed centrifugal mixing for 3 min to obtain a composite material-modified polyaspartate polyurea coating.
[0081] (3) Coating the film layer:
[0082] Coat the polyaspartate polyurea coating obtained in step (2) on the surface of a Q235 carbon steel substrate that has been surface-treated (polished from 60 mesh to 220 mesh, then ultrasonically cleaned with a degreasing solution to remove oil stains and impurities on the surface, and finally dried in an oven on the surface of the sample). Place it in an oven at 60 °C and dry and cure for 48 h, then a silane-modified graphene oxide / polyaspartate polyurea composite coating is obtained on the surface of the Q235 carbon steel, and the dry film thickness of the composite coating is 100 ± 10 μm.
[0083] Performance testing
[0084] Perform the following characterizations and tests on Example 1 and Comparative Examples 1-3:
[0085] 1. Microscopic morphology test of the composite material
[0086] Place the prepared graphene oxide and GO-PDA under a scanning electron microscope for observation, and the obtained morphological structure and element distribution are as Figure 1 shown. It can be seen that PDA has achieved uniform growth on the surface of graphene oxide, which reduces the agglomeration and wrinkles of graphene oxide itself.
[0087] 2. Coating adhesion test
[0088] Perform adhesion tests on the coatings prepared in Example 1 and Comparative Examples 1-3 using a pull-off tester, and the results are as Figure 2 shown.
[0089] The results show that the adhesion of the GO-PDA / polyaspartate polyurea coating in Example 1 of the present invention reaches 16.5 Mpa. In Comparative Example 1, without adding the polydopamine-modified graphene oxide composite material, the adhesion of the polyaspartate polyurea composite coating is 9.23 Mpa. In Comparative Example 2, the adhesion of the polyaspartate polyurea coating with unmodified graphene oxide added is 11.38 Mpa. In Comparative Example 3, the adhesion of the polyaspartate polyurea coating with silane-modified graphene oxide is 11.97 Mpa.
[0090] 3. Electrochemical impedance spectroscopy experiment of the coating
[0091] The coatings prepared in Example 1, Comparative Example 1, and Comparative Example 2 were immersed in a 3.5 wt.% sodium chloride solution, and electrochemical tests were carried out while immersed in the 3.5 wt.% sodium chloride solution. After 100 days of electrochemical testing, the impedance modulus results are as Figure 3 shown.
[0092] The results show that the low-frequency impedance modulus of Example 1 of the present invention always remains at 10 11 Ω·cm 2 , while the low-frequency impedance modulus of Comparative Example 1 always decreases from 10 10 to 10 9 Ω·cm 2 , and the low-frequency impedance modulus of Comparative Example 2 only remains at 10 10 Ω·cm 2 . It is proved that after the polyaspartate polyurea of the present invention incorporates the polydopamine-modified graphene oxide composite material, it can enhance the physical barrier performance of the coating and enhance the long-term corrosion resistance.
[0093] The above embodiments of the present invention are merely examples given to clearly illustrate the present invention, and are not intended to limit the implementation manners of the present invention. For those of ordinary skill in the art, other different forms of changes or modifications can be made on the basis of the above description. It is not necessary and impossible to enumerate all the implementation manners here. Any modifications, equivalent replacements, and improvements made within the spirit and principle of the present invention shall be included within the protection scope of the claims of the present invention.
Claims
1. A method for preparing an aspartic acid ester polyurea coating, characterized in that: The following steps are involved: S1, dispersing graphene oxide in a buffer solution, adding dopamine-hydrochloric acid and stirring to react, to obtain polydopamine-modified graphene oxide; the mass ratio of the graphene oxide to dopamine-hydrochloric acid is 1:(0.5-3); S2, mixing the polydopamine-modified graphene oxide and aspartic acid ester evenly, adding an isocyanate curing agent and mixing evenly to obtain an aspartic acid ester polyurea coating.
2. The method for preparing the aspartic acid ester polyurea coating according to claim 1, characterized in that: In step S1, the buffer solution is a tris(hydroxymethyl)aminomethane buffer solution with a pH value of 7-9.
3. The method for preparing the aspartic acid ester polyurea coating according to claim 1, characterized in that: In step S1, the stirring reaction temperature is 25 to 80° C., and the reaction time is 5 to 32 hours.
4. The method for preparing the aspartic acid ester polyurea coating according to claim 1, characterized in that: In step S2, the mass ratio of the polydopamine-modified graphene oxide to polyaspartic acid ester is (0.05-0.5):
10.
5. The method for preparing the aspartic acid ester polyurea coating according to claim 1, characterized in that: In step S2, the amount of the isocyanate curing agent used is 65-80 wt.% of the polyaspartic acid ester.
6. The method for preparing the aspartic acid ester polyurea coating according to claim 1, characterized in that: In step S2, when the polydopamine-modified graphene oxide and aspartic acid ester are uniformly mixed, a diluent is also added, and the mass ratio of the polyaspartic acid ester to the diluent is 10:(3-6).
7. The method for preparing the aspartic acid ester polyurea coating according to claim 6, characterized in that: In step S2, the diluent is at least one of butyl acetate, xylene or propylene glycol methyl ether acetate.
8. An aspartic acid ester polyurea coating, characterized in that: The aspartic acid ester polyurea coating is prepared by the preparation method of any one of claims 1 to 7.
9. Use of the aspartic acid ester polyurea coating according to claim 8 in preparing protective materials for marine engineering equipment.
10. An aspartic acid ester polyurea coated product, characterized in that: The coating is prepared by at least partially applying the aspartic acid ester polyurea coating of claim 8 on a metal substrate and curing the coating to form a coating.